Changes in chronic graft-versus-host disease treatment over time: a15-years survey within allogeneic hematopoietic stem cell transplant centers in Germany, Austria, and Switzerland : allogeneic : adult - Denk, Alexander; Fante, Matthias Alexander; Heidenreich, Silke; Greinix, Hildegard T.; Drouet, Eva-Maria Wagner; Egger-Heidrich, Katharina; Marx, Julia; Kodzhabasheva, Darina; Krüger, William; Bug, Gesine; Wehr, Claudia; Halter, Joerg; et al. (Transplantation and cellular therapy, 2025)
Background - Chronic graft-versus-host disease (cGVHD) represents a major complication after allogeneic stem cell transplantation (alloHSCT). In 2009 and 2018 a survey among German, Austrian, and Swiss transplant centers showed a homogeneous 1st-line treatment practice, while 2nd-line treatment as well as management of progressive onset type and bronchiolitis obliterans syndrome (BOS) displayed significant heterogeneity. Since the last survey, ruxolitinib (rux) has been approved and other new agents are explored in treatment of cGVHD. - Objective - We conducted a follow-up survey in 2024 to document the impact of recent approvals and new agents on treatment pattern focusing on management of 2nd-line treatment, progressive onset type, BOS, and sclerotic manifestations. - Study design - A paper-and-pencil-based questionnaire was sent electronically to 60 German speaking centers performing alloHSCT. 20 centers responded, representing 45% of the patients receiving an alloHSCT in 2023 in Germany, Austria, and Switzerland. - Results - In 1st-line treatment of classic standard risk cGVHD, single agent prednisone represents standard of care (14/20 centers) which may be combined with calcineurin inhibitor (CNI) (4/20), while rux is used in selected cases only. In 2nd-line treatment rux is now used by the majority of centers (19/20). In the presence of cytopenia, rux remains the preferred agent (12/20) while use of extracorporeal photopheresis (ECP) is considered by 8 of 20 centers. In case of active infections, ECP is preferred by 15 of 20 centers and both agents are regarded as steroid-sparing agents in 2nd-line treatment of steroid-dependent cGVHD. Rux would be applied in the presence of active infections by 5/20 centers only. Moreover, rux (15/20) and ECP (6/20) are also preferred treatment modalities in treatment of progressive onset cGVHD. For BOS, systemic and inhalative corticosteroids, montelukast and azithromycin (FAM, 13/20), rux (15/20), ECP (17/20) and CNI (10/20) are frequently applied agents, while abatacept (8/20), belumosudil (7/20), imatinib (5/20), mycophenolate mofetil (MMF) (5/20), everolimus (4/20) and ibrutinib (3/20) are used as salvage options in selected patients only. In case of new sclerotic manifestations after failure of 2nd-line treatment including steroids, CNI and rux, most centers would use ECP (14/20), whereas subsequent or alternative salvage treatment of sclerotic manifestations remains heterogenous comprising belumosudil (13/20), ibrutinib (5/20), imatinib (5/20), rituximab (4/20), cyclosporine (3/20), tacrolimus (3/20), everolimus (3/20), sirolimus (3/20), methotrexate (3/20) and MMF (3/20). The preferred taper sequence of immunosuppressive agents in case of response applied in 12/20 centers is initial taper of steroids, followed by taper of CNI and final termination of rux. - Conclusion - The survey documents the effect of evidence and approval on clinical care with single agent prednisone representing the standard of care in 1st-line treatment while rux combined with steroids defines the new standard for 2nd-line treatment of cGVHD. ECP is used in case of contraindication for rux and both agents are also used in progressive onset cGVHD. In contrast, treatment of BOS and sclerotic cGVHD beyond 2nd-line treatment remains heterogeneous with new agents being integrated in the treatment landscape.
Online verfügbar: 5. Mai 2025, Artikelversion: 3. Juli 2025
Gesehen am 02.09.2025